AISI1045 기계구조용 탄소강의 질화 가스분위기에 따른 화합물층의 형성 및 조직변화 - 이원범; Won-beom Lee; 유광춘; Kwang-chun Yu; 김영민; Young-min Kim; 위재용; Jae-lyoung Wi (대한금속·재료학회지, 54(7), 2016)
Compound layers developed at 520 ℃ during gaseous nitriding of AISI 1045 steels were investigated. The nitriding potential (Kn) of a gas atmosphere of dissociating ammonia gas was checked by observation of the partial pressure of hydrogen gas. The microstructural evolution of the compound layer was studied by using optical microscopy and scanning electron microscopy. It was observed that the surface hardness was about 600 Hv after the nitriding treatment and the case depth was about 0.5mm after a nitriding treatment of 1440 min. The compound layer was composed of  ′(Fe4N) and ε(Fe2-3N). The thickness of the compound layer was simultaneously increased to 16 μm during the nitriding treatment of 1440 min. The kinetics of the compound layer growth were discussed with a modified Lehrer diagram of AISI 1045 steels, which was obtained from the thermodynamic calculation. †(Received January 15, 2016; Accepted March 2, 2016)